Changes in the components and biotoxicity of dissolved organic matter in a municipal wastewater reclamation reverse osmosis system. Issue 17 (1st September 2016) - Sun, Ying-Xue; Hu, Hong-Ying; Shi, Chun-Zhen; Yang, Zhe; Tang, Fang
ABSTRACT: The characteristics of dissolved organic matter (DOM) and the biotoxicity of these components were investigated in a municipal wastewater reclamation reverse osmosis (mWRRO) system with a microfiltration (MF) pretreatment unit. The MF pretreatment step had little effect on the levels of dissolved organic carbon (DOC) in the secondary effluent, but the addition of chlorine before MF promoted the formation of organics with anti-estrogenic activity. The distribution of excitation emission matrix (EEM) fluorescence constituents exhibited obvious discrepancies between the secondary effluent and the reverse osmosis (RO) concentrate. Using size exclusion chromatography, DOM with low molecular weights of approximately 1.2 and 0.98 kDa was newly formed during the mWRRO. The normalized genotoxicity and anti-estrogenic activity of the RO concentrate were 32.1 ± 10.2 μg4-NQO/mgDOC and 0.36 ± 0.08 mgTAM/mgDOC, respectively, and these values were clearly higher than those of the secondary effluent and MF permeate. The florescence volume of Regions I and II in the EEM spectrum could be suggested as a surrogate for assessing the genotoxicity and anti-estrogenic activity of the RO concentrate.